Pewarisan Saham Perseroan Terbatas Kepada Warga Negara Asing Melalui Surat Wasiat - Fagustien Zaharani (Fakultas Hukum, Universitas Muhammadiyah Pontianak, 2018)
The implementation of a will for the object of inheritance in the form of shares in a limited company of domestic investment aimed at foreign nationals as recipients of a will until now has not been regulated in the Laws and Regulations in force in Indonesia. The author in this study wants to examine and analyze further about the validity of a will addressed to foreign nationals and legal protection for foreign nationals who obtain an inheritance in the form of shares from a will. The research method used is normative legal research, namely legal research carried out by examining library materials or secondary legal materials while the problem approach is carried out using a law approach and conceptual approach. The results of the study indicate that making a will is not limited to the citizenship of a person, either an Indonesian citizen or a foreign national. A will addressed to a foreign national must be made in the form of an open will (open bar testament) made before a Notary who is domiciled in the country where the object of inheritance is located. Legal protection for the transfer of shares due to inheritance to foreign citizens is to change the status of the company into a foreign investment limited liability company in accordance with the provisions in Indonesia.